ANALISIS BUTIR SOAL PENILAIAN AKHIR SEMESTER (PAS) GANJIL TAHUN AJARAN 2023/2024 PADA MATA PELAJARAN MATEMATIKA UPT SD NEGERI 228 PINRANG - Rismawati, Rismawati; Nurul Mukhlisa; Lukman, Lukman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research aims to analyze the quality of test items in the Odd Semester Final Examination (SFE) for the academic year 2023/2024 in Mathematics at UPT SD Negeri 228 Pinrang. The subjects of the study include the blueprint of the exam, the exam items, and the answer sheets from students in grades IV, V, and VI. Data were collected through documentation techniques involving Mathematics PAS exam questions and student answer sheets. Data analysis was conducted using a quantitative descriptive approach. Based on the results of data analysis, in terms of the content validity of the questions they are valid, in terms of the validity of the criteria most of them are invalid, in terms of reliability there are reliable and unreliable questions, in terms of the level of difficulty the questions have a disproportionate level of difficulty, in terms of the Discrimination, the questions have good Discrimination. Additionally, the effectiveness of distractors shows both effective and ineffective distractors in the exam items.